2014
DOI: 10.1088/0004-637x/794/2/103
|View full text |Cite
|
Sign up to set email alerts
|

The Next Generation Virgo Cluster Survey. Viii. The Spatial Distribution of Globular Clusters in the Virgo Cluster

Abstract: We report on a large-scale study of the distribution of globular clusters (GCs) throughout the Virgo cluster, based on photometry from the Next Generation Virgo Cluster Survey (NGVS), a large imaging survey covering Virgo's primary subclusters (Virgo A=M87 and Virgo B=M49) out to their virial radii. Using the g o , (g − i ) o color-magnitude diagram of unresolved and marginally resolved sources within the NGVS, we have constructed 2-D maps of the (irregular) GC distribution over 100 square degrees to a depth o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
199
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(224 citation statements)
references
References 158 publications
(236 reference statements)
18
199
1
6
Order By: Relevance
“…Therefore dwarf galaxies may not be significant contributors to the population of intra-cluster globular clusters found in the Virgo cluster (e.g. Williams et al 2007;Lee et al 2010;Durrell et al 2014). For dwarf galaxies that are infalling into the cluster for the first time, the mass-loss can be expected to be even weaker.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore dwarf galaxies may not be significant contributors to the population of intra-cluster globular clusters found in the Virgo cluster (e.g. Williams et al 2007;Lee et al 2010;Durrell et al 2014). For dwarf galaxies that are infalling into the cluster for the first time, the mass-loss can be expected to be even weaker.…”
Section: Discussionmentioning
confidence: 99%
“…For galaxies in the local universe ( 30 Mpc), the properties of the stellar halos can also be addressed using discrete tracers such as globular clusters (GCs) and planetary nebulae (PNe). Observations show that the red GC populations have numberdensity profiles consistent with that of the stars in the parent galaxy, while the blue GCs are spatially more extended in the intracluster space and trace the metal-poor component of the halo (Forbes et al 2012;Pota et al 2013;Durrell et al 2014;Cantiello et al 2015;Hilker et al 2015). In the Hydra cluster, the location of blue GCs coincides with a group of dwarf galaxies under disruption, suggesting a young stellar halo that is still forming (Arnaboldi et al 2012;Hilker et al 2015).…”
Section: Introductionmentioning
confidence: 85%
“…The recent survey of the GC population in the Virgo cluster around M 87 by Durrell et al (2014) showed the presence of an ICGC population, mostly associated with blue GCs (see further discussion in Sect. 6.3).…”
Section: Icl In Virgo: Nature and Number Of Its Progenitor Galaxiesmentioning
confidence: 96%
“…We can now also check whether the Virgo ICL associated with the ICPN population could be related to the blue GC population that is found around M 87, that has a shallower and more extended surface density profile than the red GCs, which trace the stellar halo light (Côté et al 2001;Tamura et al 2006;Strader et al 2011;Forte et al 2012;Durrell et al 2014). To do this, we need to estimate the total number of GCs associated with M 33 and LMC-like systems.…”
Section: Icl In Virgo: Nature and Number Of Its Progenitor Galaxiesmentioning
confidence: 99%